Business success and the architectural practice of Sir George Gilbert Scott, c.1845–1878: a study in hard work, sound management and networks of trust. Issue 6 (18th August 2017) - McKinstry, Sam; Ding, Ying Yong
Abstract: The study which follows explores the management of Sir George Gilbert Scott's architectural practice, which was responsible for the very large output of over 1000 works across the Victorian period. The Scott practice has been seen by some as a predecessor of the modern, large-scale architectural office. Employing insights from Max Weber's Protestant Ethic ( PE), the article examines Scott's motivation as an architect, the nature of his leadership and the detailed structuring and management of his office and of architectural projects. This is followed by a short case study relating to Scott's rebuilding of Glasgow University from 1865–1870. Finally, there are some reflections on the article's implications for further historical studies of businessmen and businesses from different periods through the lens of Weber's PE .